2011
DOI: 10.1002/ijc.26498
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma triggers an immunoevasive program involving galectin‐1‐dependent modulation of T cell and dendritic cell compartments

Abstract: The immunosuppressive strategies devised by neuroblastoma (NB), the most common solid extracranial childhood cancer, are poorly understood. Here, we identified an immunoevasive program triggered by NB through secretion of galectin-1 (Gal-1), a multifunctional glycan-binding protein. Human and mouse NB cells express and secrete Gal-1, which negatively regulates T cell and dendritic cell function. When injected subcutaneously in syngeneic A/J mice, knockdown transfectants expressing low amounts of Gal-1 (NXS2/L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 50 publications
(80 reference statements)
3
64
1
Order By: Relevance
“…46 Recently, we could demonstrate that NB promotes iDC to promote its own survival. 20 Here, we extended this finding and showed that targeted HO-1 inhibition in NB cells could abrogate HO-1-mediated blockade of DC maturation. As iDCs produce IL-10 and, additionally, express HO-1 at higher levels, 21 a further characterization of these cells and their immunosuppressive function in relation to HO-1 in NB is urgently needed.…”
Section: Cancer Therapy and Preventionsupporting
confidence: 52%
See 3 more Smart Citations
“…46 Recently, we could demonstrate that NB promotes iDC to promote its own survival. 20 Here, we extended this finding and showed that targeted HO-1 inhibition in NB cells could abrogate HO-1-mediated blockade of DC maturation. As iDCs produce IL-10 and, additionally, express HO-1 at higher levels, 21 a further characterization of these cells and their immunosuppressive function in relation to HO-1 in NB is urgently needed.…”
Section: Cancer Therapy and Preventionsupporting
confidence: 52%
“…Passages between 5 and 12 were used for the in vitro and in vivo experiments. 20 Zinc (II) protoporphyrin IX (ZnPPIX) (Frontier Scientific Europe, Carnforth, UK) and cobalt protoporphyrin (CoPPIX) (Sigma Aldrich) were both dissolved in 0.2 M NaOH for the in vitro experiments, distilled water. was added up to 1 mg/ml (pH 7.4 adjusted with 1 M HCl) (Millipore, Schwalbach, Germany).…”
Section: Cell Culture and Viability Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Gal-1 is known to define autoimmunity, 70 inflammatory neurodegeneration, 71 cardiac inflammation, 72 and tumor escape. 73 74 and recent data confirm that it is not only expressed by the placenta itself 75 but also in uterine NK cells, 76 tolerogenic DCs, 55 and recent data show its importance when expressed in uterine MCs. 58 Pregnancies of Gal-1-deficient mice were first described as normal as the number of born embryos was apparently unaffected by this mutation.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 70%